Strategi Komunikasi Pramuwisata dalam Pengembangan Wisata Air Terjun Tumpak Sewu Desa Sidomulyo Kecamatan Pronojiwo Kabupaten Lumajang - Salsabillah Handini (Journal of Management, Education and Communication, 2025)
Tour guides, as the spearhead of direct interaction with tourists, play an important role in supporting the advancement of local tourism. This study aims to examine the communication strategies implemented by tour guides in the development of the Tumpak Sewu Waterfall tourist destination in Sidomulyo Village, Pronojiwo District, Lumajang Regency. The method used in this study is a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results of the study show that there are three main communication strategies implemented by tour guides: (1) Communication strategy through social media, which is carried out by consistently sharing informative content and tourism promotions to attract tourists; (2) Communication strategy through cooperation, namely establishing synergy with local businesses, village governments, and nature lover communities to strengthen the tourism ecosystem; and (3) Communication strategy through changing people's mindset, which aims to build awareness and active participation of the local community in preserving the environment and providing the best service to tourists